2017
DOI: 10.1371/journal.pone.0172804
|View full text |Cite
|
Sign up to set email alerts
|

Physical performance analysis: A new approach to assessing free-living physical activity in musculoskeletal pain and mobility-limited populations

Abstract: BackgroundAccurate measurement of physical performance in individuals with musculoskeletal pain is essential. Accelerometry is a powerful tool for this purpose, yet the current methods designed to evaluate energy expenditure are not optimized for this population. The goal of this study is to empirically derive a method of accelerometry analysis specifically for musculoskeletal pain populations.MethodsWe extracted data from 6,796 participants in the 2003–4 National Health and Nutrition Examination Survey (NHANE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 35 publications
(58 reference statements)
0
24
0
Order By: Relevance
“…Consistently, the Initiative on Methods, Measurement, and Pain Assessment in Clinical Trials (IMMPACT) 8,9 and the International Classification of Functioning, Disability and Health (ICF) 10 recommend comprehensively assessing physical function, with PROs, performance-based (which capture functional capacity during a time-limited standard test), and objective assessments (ambulatory measurement of daily step-count via accelerometers across a specified time period). 11 Studies evaluating the relationship between the different aspects of physical function in chronic pain have generally found conflicting results on the association between PROs and accelerometer-measured physical function. [12][13][14] They found a small to moderate association between PROs and performanced based physical function, [15][16][17][18] as well as between accelerometer-measured physical function and PROs.…”
Section: Introductionmentioning
confidence: 99%
“…Consistently, the Initiative on Methods, Measurement, and Pain Assessment in Clinical Trials (IMMPACT) 8,9 and the International Classification of Functioning, Disability and Health (ICF) 10 recommend comprehensively assessing physical function, with PROs, performance-based (which capture functional capacity during a time-limited standard test), and objective assessments (ambulatory measurement of daily step-count via accelerometers across a specified time period). 11 Studies evaluating the relationship between the different aspects of physical function in chronic pain have generally found conflicting results on the association between PROs and accelerometer-measured physical function. [12][13][14] They found a small to moderate association between PROs and performanced based physical function, [15][16][17][18] as well as between accelerometer-measured physical function and PROs.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is important to recognize that self-reported physical activity captures the capability to complete a given task, while the ability to measure the actual performance is limited (Smuck et al. 2017). Accelerometer-based measures of physical activity allow us to evaluate if patients with hip dysplasia change objectively measured physical activity profile, alongside with subjective measured levels of improved pain, physical function, and quality of life after PAO.…”
mentioning
confidence: 99%
“…55 For future studies, it has been suggested that it is possible to modify and analyze novel intervals for accelerometer data to detect varying activity levels of real-life physical performance. 56 The wrist is the preferred location for sleep measures and, while the waist has been reported as the optimal location for recording a wide range of physical activity, 57 a previous study found much lower compliance rates for waist sensors compared to wrist sensors (i.e., 65% versus 99% wear time). 58 This finding prompted the NHANES program to switch placement from the waist to the wrist, which did result in improved compliance rates.…”
Section: Discussionmentioning
confidence: 99%